Imagine a mouse and an elephant: Hemispheric asymmetries of imagination. Issue 3 (4th May 2017) - Dural, Seda; Çetinkaya, Hakan; Güntürkün, Onur
ABSTRACT: The present study aimed to explore the existence of an asymmetrical bias in the imagination of pairs of objects of unequal size. We assumed that such pairs are conceptualized with the smaller object being placed on the left, creating an ascending size order from left to right. Such a bias could derive from a cognitive strategy known from the mental number line. Sixty-four participants were instructed to imagine stimulus-pairs that were staggered from those showing very prominent intra-pair size differences (e.g., elephant vs. mouse) to very low size differences (e.g., orange vs. apple). The results showed that the tendency to imagine the bigger object on the right side increases with the size difference of the two stimuli. Such a visual field bias was also present in stimulus-pairs including numbers so that the participants imagined smaller and larger numbers on the left and the right side of the visual fields, respectively. Taken together, our findings could imply that the left-to-right orientation observed in our object imagining task may share the same cognitive mechanism as the mental number line.